Integration of Islamic values in undergraduate nursing program: An expository analysis - Nurumal, Mohd. Said; Jamaludin, Thandar Soe Sumaiyah; Ahmad, Norfadzilah; Muhammad, Siti Aeshah @ Naznin; Mei Chan, Chong (IIUM Press, 2019)
Nursing is a caring profession which has sympathy, compassion, and helping others inherently which is known as soft skills in current modern day. Those skills are the foundation of Islamic values for a Muslim graduate nurse who should pose. Hence, this study aimed to address the importance of integrating Islamic values in the undergraduate nursing program. This paper provides an account that is intended as an expository analysis method for the integration of Islamic values in the undergraduate nursing program. Paying attention not only to the material world of human but also his or her soul and spirituality dimension. Thus, the subject area to investigate the effect of the integration on Islamic values or soft skills in the undergraduate nursing program is extremely recommended for future study.